2020
DOI: 10.1136/bmjopen-2020-040129
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in coronavirus disease (COVID-19): a systematic review and meta-analysis

Abstract: ObjectiveTo assess the sex difference in the prevalence of COVID-19 confirmed cases.DesignSystematic review and meta-analysis.SettingPubMed, Cochrane Library and Google Scholar were searched for related information. The authors developed a data extraction form on an Excel sheet and the following data from eligible studies were extracted: author, country, sample size, number of female patients and number of male patients. Using STATA V.14 for analysis, the authors pooled the overall prevalence of men and/or wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
174
13
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(221 citation statements)
references
References 84 publications
26
174
13
8
Order By: Relevance
“…There were 46 men (50.5%) and 45 women (49.5%) in this study, with men being slightly more common than females. This is consistent with the results of Abate et al (2020) systematic reviews have also indicated that COVID-19 is more common in men than in women.…”
Section: Discussionsupporting
confidence: 92%
“…There were 46 men (50.5%) and 45 women (49.5%) in this study, with men being slightly more common than females. This is consistent with the results of Abate et al (2020) systematic reviews have also indicated that COVID-19 is more common in men than in women.…”
Section: Discussionsupporting
confidence: 92%
“…When comparing men and women of similar social and economic situations, differences between sexes are generally reduced [ 28 , 30 ]. Another possible reason for the sex differences in COVID-19 mortality is differences in lifestyle, such as smoking and alcohol consumption between men and women [ 31 ]. A systematic review including evidence from five studies found that smokers were 1.4 times more likely than non-smokers to have severe symptoms of COVID-19 and were around 2.4 times more likely to need mechanical ventilation, to be admitted to an intensive care unit or to die compared with non-smokers [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review including evidence from five studies found that smokers were 1.4 times more likely than non-smokers to have severe symptoms of COVID-19 and were around 2.4 times more likely to need mechanical ventilation, to be admitted to an intensive care unit or to die compared with non-smokers [ 32 ]. Thus, the higher risk-taking behavior in men than in women, including a higher prevalence of male smokers, may also contribute to sex differences in COVID-19 mortality [ 31 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increases in available data it is possible to interrogate the statistics further and ask whether differences such as infection rates, age and co-morbidities can explain the sex differences in the outcomes of COVID19, ( Abate et al, 2020 ). It appears that none can.…”
Section: Introductionmentioning
confidence: 99%